2016
DOI: 10.1007/s10508-016-0740-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Lifetime Extradyadic Sex Using a Hybrid of Randomized Response Technique and Crosswise Design

Abstract: The prevalence of extradyadic sex (EDS) tends to be underestimated due to underreporting in national surveys, which use direct questioning. Self-administered questionnaires can reduce this response bias but may cause the anxiety of privacy exposure. Randomized Response Technique (RRT) can ensure participants' confidentiality under the randomized design of indirect questions to and was found to yield more valid estimates of sexual or other sensitive behaviors than direct questions. This study estimated the EDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…By mathematical reasoning, one can calculate the latter probability based on the overall proportion of positive answers in the whole sample (details followed in the Materials and Methods section). It has been used to explore many sensitive issues such as illicit drug use, 15 risk sexual behaviors involvement, 16 , 17 noncompliant behavior for drivers, 18 and voter turnout measurement, 19 and so on.…”
mentioning
confidence: 99%
“…By mathematical reasoning, one can calculate the latter probability based on the overall proportion of positive answers in the whole sample (details followed in the Materials and Methods section). It has been used to explore many sensitive issues such as illicit drug use, 15 risk sexual behaviors involvement, 16 , 17 noncompliant behavior for drivers, 18 and voter turnout measurement, 19 and so on.…”
mentioning
confidence: 99%
“…Among Taiwanese individuals, lifetime incidence of extradyadic sexual activity was 27.3% among married people and 25.5% among the unmarried (Tu & Hsieh, 2017). In a random sample of Norwegian heterosexual couples, in 6% of couples the woman and in 13% of couples the man had an extradyadic sexual partner, and in 4% of couples both partners engaged in extradyadic sex (Træen & Martinussen, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Infidelity was more common among cohabitators (Tu & Hsieh, 2017; Whisman & Snyder, 2007). Roberson et al (2017) found four latent classes of relationships among emerging adults: committers, casual daters, settlers, and volatile daters.…”
Section: Resultsmentioning
confidence: 99%
“…Ostapczuk et al (2009) studied attitudes toward foreigners, whereas Perri et al (2016) dealt with induced abortion and migrants’ irregular presence. Hsieh et al (2010) considered the proportion of illegal cable TV in Taiwan, and Tu and Hsieh (2017) studied extradyadic sexual behavior. De Jong et al (2012) introduced a polytomous item RRT that increases reporting sexual proclivities related to DQ.…”
Section: Introductionmentioning
confidence: 99%